KUALITAS PEMBELAJARAN E-LEARNING BERDASARKAN PERSEPSI MAHASISWA - Desty Prawatiningsih; Nur Asia T (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: The goal of this research is to know the quality of the distance learning using by E-learning in pandemi Covid-19. The method of this research is study Survey by using Descriptive Quantitative Analysis. The research subjects were students of the Da’wah Faculty of UIN Sultan Maulana Hasanuddin Banten with a total sample of 314 respondents and data collection techniques with Non Probability Sampling with Accidental Sampling in the form of a questionnaire. The results of the study measure the quality of e-learning according to the student’s perspective seen from: the level of quality of e-learning at the Da’wah Faculty in terms of quality: learning design, learning activities, delivery strategies, interaction between students and students and students with lecturers, learning assistance services, interaction students with teaching materials, collaboration, feedback systems, and learning assessments. The results of this study indicate that in general the quality of e-learning based on student perceptions includes good enough criteria.Keywords: E-Learning, Quality, PerceptionAbstrak: Penelitian pembelajaran e-learning untuk mengetahui kualitas pembelajaran jarak jauh secara e-learning dalam kondisi pandemi covid-19. Metode penelitian adalah studi survei dengan teknik analisis data deskriptif. Subjek penelitian adalah mahasiswa fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten dengan jumlah sampel sebanyak 314 responden dan teknik pengumpulan data dengan Non Probability Sampling jenis Accidental Sampling dalam bentuk kuesioner. Penelitian ini mengukur kualitas e-learning menurut perspektif mahasiswa dilihat dari tingkat kualitas pembelajaran e-learning yaitu kualitas rancangan pembelajaran, kegiatan pembelajaran, strategi penyampaian, interaksi antar mahasiswa dengan mahasiswa dan mahasiswa dengan dosen, layanan bantuan pembelajaran, interaksi mahasiswa dengan bahan ajar, kolaborasi, sistem umpan balik, serta penilaian pembelajaran. Hasil penelitian ini menunjukkan secara umum mutu pembelajaran e-learning berdasarkan persepsi mahasiswa termasuk kriteria cukup baik.Kata kunci: E-Learning, Kualitas, Persepsi